Talleres de capacitación para el desarrollo de actividades científicas dirigido a docentes de la escuela fiscal nocturna Vicente Anda Aguirre de la ciudad de Latacunga, período 2012 – 2013 - Tapia Chacón, Celia Mercedes (2015)
The present investigation work, allowed to implant in the School of Basic Education Vicente Anda Aguirre of Latacunga, county of Cotopaxi, a series of training shops to develop scientific activities directed to the educational ones, with the main objective of offering special attention to the problem of not generating investigation and scientific activities to the students and the same professors that affect in the study habits and in the academic yield. The investigation recaptures this purpose textually and to validate the proposal an investigation methodology it was applied that provided us important data about the situation for which crosses the educational institution as for the development and generation of scientific activities. The obtained results manifest the direct influence of the inadequate study habits evidently with the academic acting; they allow to demonstrate the unit of the instrument in the practice of the tutorship, as well as to quantify and to evidence the necessity to undertake the actions to develop shops that are in benefit of the educational community....